2013
DOI: 10.21236/ada588181
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation of Traumatically Induced Axonal Injury in a Three-Dimensional (3-D) Finite Element Model (FEM) of the Human Head During Blast-Loading

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden, to Department of Defense, Washington Headquarters Services, Directorate for Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Once the blast enters the skull, the effect on brain tissue is still under investigation. However, computer simulations and test data suggest that stress waves induce shear, spallation, implosion, and inertial effects within the brain tissue ( 69 ), leading to diffuse axonal injury in white matter regions ( 75 ). Models also suggest that the enhancement effects of pressure waves passing through the skull and blast reflection at the interface of different materials cause neuronal damage and tissue disruption, typically in the traditional coup and contrecoup regions ( 75 ).…”
Section: Blastmentioning
confidence: 99%
“…Once the blast enters the skull, the effect on brain tissue is still under investigation. However, computer simulations and test data suggest that stress waves induce shear, spallation, implosion, and inertial effects within the brain tissue ( 69 ), leading to diffuse axonal injury in white matter regions ( 75 ). Models also suggest that the enhancement effects of pressure waves passing through the skull and blast reflection at the interface of different materials cause neuronal damage and tissue disruption, typically in the traditional coup and contrecoup regions ( 75 ).…”
Section: Blastmentioning
confidence: 99%
“…35 Ultimately, exposure to blast results in neuronal damage and tissue disruption, often detected in the traditional coup and contrecoup regions, and diffuse axonal injuries caused by induced stress and strains within the living tissues of the brain. 36 Because these stresses and strains cannot be directly measured, measurement of ICP can provide a useful surrogate method for estimating energy deposition, particularly because ICPs have shown to correlate with fatality rates. 37 In addition, computational modeling can provide significant insight into transmission and dissipation of blast energy through and into the brain tissue.…”
Section: Penetrating Impactmentioning
confidence: 99%
“…[38][39][40][41] Based upon these simulations, stress waves induce shear, spallation, implosion, and inertial effects within the brain tissue. 33 Computational models have also shown that peak stresses and strains within the brain correlate with high-pressure regions at the coup and contrecoup locations 30,36 ; the coup/ contrecoup regions are shown to be more exposed to high magnitude pressures, and consequently greater injury, due to the reflection of the shock wave at the interface of the brain with the skull. 42…”
Section: Penetrating Impactmentioning
confidence: 99%
“…Grujicic et al [10] propose that rotational motion and acceleration/deceleration are not applicable in blast-induced trauma scenarios. Conversely, an investigation by Dagro et al [11] supports the notion that rotational loading is relevant to blast events. In addition, Elder [12] discovered injuries reminiscent of DAI by exposing live animals to blast pressure events, and attributes these injuries to rotational acceleration.…”
Section: Introductionmentioning
confidence: 96%